2016
DOI: 10.1016/j.hpb.2016.03.227
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) in Biliary tract cancer

Abstract: Introduction: Overexpression of epidermal growth factor receptor (EGFR) in tumor cells has been associated with a poor prognosis, but also offers the therapeutic option of pharmacologically targeting these receptors. The role of EGFR in hepatic malignancies is not clearly understood. The aim of this study was to analyze the expression of the EGFR in gallbladder cancer and cholangiocarcinomas. Methods: Paraffin-embedded samples from 60 patients with carcinomas of the biliary tract were studied. Clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…EGFR (synonym ErbB1, HER1) plays a crucial role in cancer proliferation, cell mortality, angiogenesis, cell adhesion, and metastasis through multiple downstream pathways (ERK/MAPK, PI3K-AKT, SRC, PLC-γ1-PKC, JNK, JAK-STAT) [ 115 , 116 , 117 ]. The overexpression of EGFR in GBC is common, with a frequency of 44–77% [ 118 , 119 , 120 ], and is associated with a worse prognosis [ 121 ]. At the moment, data on the effect of anti-EGFR therapy in GBC patients is disappointing.…”
Section: Therapymentioning
confidence: 99%
“…EGFR (synonym ErbB1, HER1) plays a crucial role in cancer proliferation, cell mortality, angiogenesis, cell adhesion, and metastasis through multiple downstream pathways (ERK/MAPK, PI3K-AKT, SRC, PLC-γ1-PKC, JNK, JAK-STAT) [ 115 , 116 , 117 ]. The overexpression of EGFR in GBC is common, with a frequency of 44–77% [ 118 , 119 , 120 ], and is associated with a worse prognosis [ 121 ]. At the moment, data on the effect of anti-EGFR therapy in GBC patients is disappointing.…”
Section: Therapymentioning
confidence: 99%
“…The overexpression population of EGFR in GBC was observed between 44 and 77% of patients in different independent studies. [133][134][135] Elevated expression of EGFR in GBC tissues was positively correlated with poor prognosis of the patients. 136 We also found that somatic mutations of EGFR were quite low ranging from 2.5 to 3.9% in GBC patients.…”
Section: Her2mentioning
confidence: 99%